CD44 expression in the tumor periphery predicts the responsiveness to bevacizumab in the treatment of recurrent glioblastoma. (5th February 2021) - Nishikawa, Masahiro; Inoue, Akihiro; Ohnishi, Takanori; Yano, Hajime; Kanemura, Yonehiro; Kohno, Shohei; Ohue, Shiro; Ozaki, Saya; Matsumoto, Shirabe; Suehiro, Satoshi; Nakamura, Yawara; Shigekawa, Seiji; et al.
Abstract: Antiangiogenic therapy with bevacizumab (Bev), a monoclonal antibody targeting vascular endothelial growth factor (VEGF), is a common treatment for recurrent glioblastoma (GBM), but its survival benefit is limited. Resistance to Bev is thought to be a major cause of ineffectiveness on Bev therapy. To optimize Bev therapy, identification of a predictive biomarker for responsiveness to Bev is required. Based on our previous study, we focused on the expression and functions of CD44 and VEGF in the Bev therapy. Here, we analyze a relationship between CD44 expression and responsiveness to Bev and elucidate the role of CD44 in anti‐VEGF therapy. CD44 and VEGF expression in the tumor core and periphery of 22 GBMs was examined, and the relationship between expression of these molecules and progression‐free time on Bev therapy was analyzed. The degree of CD44 expression in the tumor periphery was evaluated by the ratio of the mRNA expression in the tumor periphery to that in the tumor core (P/C ratio). VEGF expression was evaluated by the amount of the mRNA expression in the tumor periphery. To elucidate the roles of CD44 in the Bev therapy, in vitro and in vivo studies were performed using glioma stem‐like cells (GSCs) and a GSC‐transplanted mouse xenograft model, respectively. GBMs expressing high P/C ratio of CD44 were much more refractory to Bev than those expressing low P/C ratio of CD44, and the survival time of the former was much shorter than that of the latter. In vitro inhibition of VEGF with siRNA or Bev‐activated CD44 expression and increased invasion of GSCs. Bev showed no antitumor effects in mice transplanted with CD44‐overexpressing GSCs. The P/C ratio of CD44 expression may become a useful biomarker predicting responsiveness to Bev in GBM. CD44 reduces the antitumor effect of Bev, resulting in much more highly invasive tumors. Abstract : In this research, we analyze a relationship between CD44 expression and responsiveness to Bev and elucidate the role of CD44 in anti‐VEGF therapy. These results indicate CD44 will be a useful biomarker for predicting responsiveness to bevacizumab and may serve as a therapeutic target in both primary and recurrent GBMs.